Whistleblowing System: The Effective Solution to Prevent Financial Accounting Fraud? - Sari, Kintan Kartika (Politeknik Ganesha Medan, 2024)
The whistleblowing system and internal company management are crucial in supporting the growth of integrity and good corporate governance. This research aims to identify the factors affecting implementing a whistleblowing system in preventing financial fraud and its relationship with good corporate governance. The method used is a Systematic Literature Review involving the search for relevant articles and publications based on predetermined inclusion and exclusion criteria. Using studies from the last five years from Emerald, Sinta Sage, Springer, Taylor & Francis, Korea Science, and Frontiers, 19 studies were selected. The literature analysis found that organizational support, protection for whistleblowers, an ethical work environment, and internal factors such as attitudes and motivations, as well as external factors like company size and organizational culture, are crucial to the effectiveness of the whistleblowing system. The conclusion of this research underscores that the whistleblowing system plays a key role as a moderating variable in the relationship between the influencing factors and good corporate governance, offering practical recommendations for developing and implementing an effective whistleblowing system. This research provides valuable contributions to the development of knowledge in accounting and finance as well as management practices and corporate policies, emphasizing the importance of a supportive environment and adequate protection for whistleblowers.